2014
DOI: 10.1007/s00520-014-2237-9
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and safety of a reduced duration of therapy of colony-stimulating factor in a dose-dense regimen

Abstract: PurposeThe risk of febrile neutropenia (FN) in cancer patients receiving chemotherapy is mainly due to the type of chemotherapy regimen and the presence of specific risk factors in patients. The recent trend of using a dose-dense treatment schedule has enhanced the risk of FN. In the present prospective study, we evaluated the feasibility of a reduction of duration of therapy with colony-stimulating factor (G-CSF) in a dose-dense regimen.MethodsBetween June 2002 and December 2011, 107 patients with a new diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Most of the current cancer regimens are associated with a 10-20% risk of neutropenia and breast cancer patients treated with a dose-dense anthracycline/taxane-based regimen, such as TAC, have > 20% risk of developing febrile neutropenia [10]. To help mitigate this safety risk, prophylactic use of G-CSF is recommended when the risk of febrile neutropenia, determined by considering patient factors and the chemotherapy regimen, is estimated to be approximately 20% [11][12][13]. The neutrophil support provided by efbemalenograstim alfa, a once per cycle G-CSF, was evaluated in this study and was demonstrated to have an efficacy and safety profile similar to pegfilgrastim.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the current cancer regimens are associated with a 10-20% risk of neutropenia and breast cancer patients treated with a dose-dense anthracycline/taxane-based regimen, such as TAC, have > 20% risk of developing febrile neutropenia [10]. To help mitigate this safety risk, prophylactic use of G-CSF is recommended when the risk of febrile neutropenia, determined by considering patient factors and the chemotherapy regimen, is estimated to be approximately 20% [11][12][13]. The neutrophil support provided by efbemalenograstim alfa, a once per cycle G-CSF, was evaluated in this study and was demonstrated to have an efficacy and safety profile similar to pegfilgrastim.…”
Section: Discussionmentioning
confidence: 99%